Perancangan Project Base Learning Digital Bisnis D’gaul Drink - Alferdian Adliansyah; Ashyva Yusman; M Zibran Zaki Ramadhan; Adinda Sri Ramadhani; Faradika (Jurnal Imiah Pengabdian Pada Masyarakat (JIPM), 2024)
D'Gaul Drink is a business that sells sweet drinks that can quench thirst during the day, located at Jl. Simpang Haru no. 394G 2QJ, West Sumatra Padang City. Prepared drinks consisting of quality tea and various types of tea, and many people also want to serve it hot or cold. The author conducted interviews and documentation and created a website aimed at increasing the sales appeal of D'Gaul Drink. Apart from that, through the website the information that has been created is provided in detail, complete, and can provide a more attractive appearance. The method used in collecting data is a qualitative method by conducting interviews and documentation. The author made a visit and made direct observations to D'Gaul Drink to obtain the necessary data related to the design. This design produced a main media in the form of D'Gaul Drink Website Information Media.